PENGARUH KUALITAS PELAYANAN DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PADA MINIMARKET MUJAHIDIN MART DI PAMULANG - Submission JORAPI; Istiqomah Tuzzahroh; Sinta Sulistiani (Journal of Research and Publication Innovation, 2024)
This research aims to determine the extent to which service quality (X1) and promotion (X2) influence consumer purchasing decisions (Y) at the Mujahidin Mart minimarket in Pamulang. The method used is a quantitative descriptive method. Sampling technique using Slovin theory. Data analysis uses regression analysis, correlation coefficient, coefficient of determination analysis and hypothesis testing. The results of this research are that Service Quality (X1) and Promotion (X2) have a positive and significant effect on purchasing decisions (Y) by showing the results of f count > f table, namely f count = 150.394 which is greater than f table of 3.09 and a significant value of 0.001. Partially, the service quality variable has a positive and significant influence on purchasing decisions where the value obtained is (t count > t table), t count of 4.857 is greater than 1.985 and is significant 0.001. Simultaneously the Promotion variable has a positive and significant influence on purchasing decisions where the value obtained is (t count > t table) with a calculated f result of 7.503 which is greater than 1.985 with a significance of 0.001. So it can be said that Service Quality and Promotion have a significant simultaneous influence on purchasing decisions. Thus, H0 is rejected and H3 is accepted, meaning that Service Quality (X1) and Promotion (X2) together have a positive effect on purchasing decisions (Y).